ANALISIS GAYA KEPEMIMPINAN SIMBOLIK GUBERNUR JAWA BARAT KANG DEDI MULYADI DALAM KONTEKS BUDAYA SUNDA: STUDI LITERATUR - Alya Septiani; Eka Yulyana (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
This study examines the symbolic leadership style of Dedi Mulyadi within the framework of Sundanese culture, drawing on Bolman and Deal’s (1991; 2003) symbolic leadership theory. A descriptive qualitative approach was employed through a systematic literature review, with thematic content analysis applied to relevant academic sources. The findings reveal that Dedi Mulyadi consistently employs Sundanese cultural symbols—including traditional pangsi attire, wayang puppet characters, and the use of the Sundanese language in formal settings—as instruments for constructing collective identity and consolidating political legitimacy. Policies such as “Rabu Nyunda” and the “Purwakarta Berkarakter” program formally institutionalized local cultural values within governmental practice. These strategies are associated with increased community engagement in cultural programs and stronger local identity affiliation, as indicated by Dedi Mulyadi’s 62% vote share in the 2024 West Java gubernatorial election. Nevertheless, the approach encountered resistance from conservative groups who viewed certain cultural symbols—particularly wayang statues—as conflicting with Islamic principles, thereby generating a contestation of meanings within local political space. Distinct from prior studies that primarily address electoral or administrative dimensions of local leadership, this research specifically analyzes the symbolic-cultural dimension as a mechanism of legitimacy formation. The study contributes to the understanding of local wisdom-based leadership models as an alternative to technocratic approaches in regional governance contexts characterized by strong cultural cohesion.